2020
DOI: 10.1186/s12879-020-04955-2
|View full text |Cite
|
Sign up to set email alerts
|

Can metagenomic next-generation sequencing identify the pathogens responsible for culture-negative prosthetic joint infection?

Abstract: Background: The aims of this study were to (1) evaluate the efficacy and safety of targeted antibiotics for the treatment of culture-negative prosthetic joint infection based on metagenomic next-generation sequencing results and (2) verify the accuracy and reliability of metagenomic next-generation sequencing for identifying pathogens related to culture-negative prosthetic joint infection. Methods: Ninety-seven consecutive PJI patients, including 27 patients with culture-negative prosthetic joint infection, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 25 publications
1
39
0
Order By: Relevance
“…Interestingly, in all their samples, multiple microorganisms with multiple virulent factors were present. This and other reports 58 , 59 suggest that PJIs are polymicrobial at the microbial DNA level in a significant proportion of sequenced PJI cases, increasing the fear in the adult reconstruction orthopaedic community. This fear was confirmed by Namdari et al 58 who showed, in a series of 44 revision shoulder arthroplasties, that NGS data demonstrated that bacterial loads in revision arthroplasty are most commonly polymicrobial and a definition of infection that uses cultures is more prone to ‘probable contaminants’ than NGS.…”
Section: Introductionsupporting
confidence: 63%
“…Interestingly, in all their samples, multiple microorganisms with multiple virulent factors were present. This and other reports 58 , 59 suggest that PJIs are polymicrobial at the microbial DNA level in a significant proportion of sequenced PJI cases, increasing the fear in the adult reconstruction orthopaedic community. This fear was confirmed by Namdari et al 58 who showed, in a series of 44 revision shoulder arthroplasties, that NGS data demonstrated that bacterial loads in revision arthroplasty are most commonly polymicrobial and a definition of infection that uses cultures is more prone to ‘probable contaminants’ than NGS.…”
Section: Introductionsupporting
confidence: 63%
“…Through the analysis of patients who were misdiagnosed according to the microbial culture and mNGS results (Table 3), we found the following: 1).As we previously showed (Wang et al, 2020), mNGS can improve the pathogen detection rate in CN-PJI: patients 1, 2, and 3 all had prosthetic joint infections, and a large amount of purulent tissue and caseous necrosis were observed intraoperatively. The microbial culture results from the periprosthetic tissue were all negative, but mNGS found pathogenic bacteria 72 hours after sample collection (Mycobacterium abscess for patients 1 and 3 and Mycobacterium tuberculosis for patient 2).…”
Section: Discussionmentioning
confidence: 78%
“…For mNGS, periprosthetic tissues were homogenized as described above. The steps to perform mNGS included the following (Henan Li et al, 2018)(Wang et al, 2020: (1) Nucleic acid extraction: 500 ml of periprosthetic tissue homogenate was obtained, ceramic beads were utilized to break the cell walls, and total genomic DNA was extracted using a TIANamp Micro DNA Kit (DP316, Tiangen Biotech). (2) Library construction and sequencing: DNA libraries were constructed and sequenced according to the standard protocol of the BGISEQ-500 sequencing platform (BGI-Tianjin, Tianjin, China).…”
Section: Mngs Of Periprosthetic Tissue Specimens Collected Intraoperativelymentioning
confidence: 99%
“… 69 However, the detection of these pathogens cannot be considered automatically as a contaminant, and the potential existence of a ‘synovial microbiome’ opens many questions that need further research. In this sense, a recent study 73 showed that antibiotic therapy guided by the results of metagenomic next-generation sequencing was associated with a similar outcome to empirical therapy, with fewer undesired side effects.…”
Section: Biomolecular Techniquesmentioning
confidence: 99%